Stres i zespół wypalenia zawodowego jako bariery innowacyjności - Jankowska-Mihułowicz, Marzena (Stress and Burnout Syndrome as Barriers to Innovation, 2006)
In this paper there were presented nature and reasons of a stress and the burnout syndrome. There was explained, why they are the barriers that prevents workers innovation, and what should be changed in Polish organizations in order to eliminate those social problems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 90-97